2016
DOI: 10.1002/2016jc011674
|View full text |Cite
|
Sign up to set email alerts
|

Surface layer temperature inversion in the Bay of Bengal: Main characteristics and related mechanisms

Abstract: Surface layer temperature inversion (SLTI), a warm layer sandwiched between surface and subsurface colder waters, has been reported to frequently occur in conjunction with barrier layers in the Bay of Bengal (BoB), with potentially commensurable impacts on climate and postmonsoon tropical cyclones. Lack of systematic measurements from the BoB in the past prevented a thorough investigation of the SLTI spatiotemporal variability, their formation mechanisms, and their contribution to the surface temperature varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 28 publications
3
60
0
Order By: Relevance
“…When strong surface heat loss occurs in areas with strong salinity stratification, vertical temperature inversions tend to form (Drushka et al, 2014;Girishkumar et al, 2013;Thadathil et al, 2016). The analysis of historical data (Thadathil et al, 2002) and measurements from Argo floats (Thadathil et al, 2007;Thompson et al, 2006) have indicated that organized surface layer temperature inversions occur along the coastal regions of the western and northeastern parts of the BOB during the winter.…”
Section: Seasonal Variations Of the Upper Ocean Stratificationmentioning
confidence: 99%
“…When strong surface heat loss occurs in areas with strong salinity stratification, vertical temperature inversions tend to form (Drushka et al, 2014;Girishkumar et al, 2013;Thadathil et al, 2016). The analysis of historical data (Thadathil et al, 2002) and measurements from Argo floats (Thadathil et al, 2007;Thompson et al, 2006) have indicated that organized surface layer temperature inversions occur along the coastal regions of the western and northeastern parts of the BOB during the winter.…”
Section: Seasonal Variations Of the Upper Ocean Stratificationmentioning
confidence: 99%
“…From Figure c, it is further evident that magnitude of temperature inversion is very weak during summer compared to winter. It is worth to note that the magnitude of temperature inversions in the AS are very small compared to the values reported from the northern BoB, where the amplitude of temperature inversions go beyond 1 °C during the peak phase of winter (Thadathil et al, ; Thangaprakash et al, ). As reported in earlier studies in the BoB, the presence of thick BL is the necessary but not the sufficient condition to the formation of temperature inversion (Girishkumar, Ravichandran, & McPhaden, ; Thadathil et al, , ).…”
Section: Resultsmentioning
confidence: 78%
“…As suggested by earlier studies, cooling of ML by net surface heat loss and/or horizontal advection and warming of BL through penetrative shortwave radiation below the ML are the important processes that leads to the formation of temperature inversions in the presence of BL (Girishkumar, Ravichandran, & McPhaden, ; Kurian & Vinayachandran, ; Thadathil et al, , ). In order to understand the relative importance of these two processes on the formation of temperature inversion in the study area, heat flux into the ML by the sum of horizontal advection and net surface heat flux ( Q net − Q pen ) and penetrative shortwave radiation absorbed at depths below the ML (Q pen ) are presented along with magnitude of temperature inversion in Figure .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations